Đúng rồi đấy
[TEX]\int {{1 \over {\sqrt {x^2 - x} }}} dx = \int {{{dx} \over {\sqrt {x(x - 1)} }}}[/TEX] Đặt [TEX]u = \sqrt {x - 1} = > \sqrt {u^2 + 1} = x2du = {{dx} \over {\sqrt {x - 1} }}\int {{{dx} \over {\sqrt {x(x - 1)} }}} = 2\int {{{du} \over {\sqrt {u^2 + 1} }}\,\,}[/TEX]. Đặt [TEX]u = tant = > du = (1 + tan^2 t)dt2\int {{{du} \over {\sqrt {u^2 + 1} }}} = 2\int {{{(1 + tan^2 t)dt} \over {\sqrt {tan^2 t + 1} }}} = 2\int {\sqrt {1 + tan^2 t} } .dt = 2\int {{{dt} \over {cost}}} = 2\int {{{costdt} \over {1 - sin^2 t}}} = 2\int {{{d(sint)} \over {1 - sin^2 t}}} = ln\left| {{{1 + sint} \over {1 - sint}}} \right| + c[/TEX].
Vậy: [TEX]I = 2ln(\sqrt x + \sqrt {x - 1} ) + c[/TEX]